Industrial applications of holonic and multi-agent systems : 9th International Conference, HoloMAS 2019, Linz, Austria, August 26-29, 2019, Proceedings /: 9th International Conference, HoloMAS 2019, Linz, Austria, August 26-29, 2019, Proceedings. (2019) - Unknown
No abstract available